2008
DOI: 10.1002/jssc.200700686
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of zinc α2‐glycoprotein‐Prolactin inducible protein complex from human seminal plasma

Abstract: Zinc alpha2-glycoprotein (ZAG) is present at high concentration in human seminal plasma, and considered as soluble homologue of MHC-I. ZAG is a well-known biomarker for prostate and breast carcinomas. We have purified a naturally occurring complex of ZAG with Prolactin inducible protein (PIP), which is also a well-known biomarker for the same. The ZAG-PIP complex has been isolated and purified by simple chromatographic techniques in a reproducible two-step process, using ion exchange and gel-permeation chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…After the cleavage of signal peptide (28 amino acid residues) the mature polypeptide is 118 residues long with theoretical molecular mass of 13 kDa and pI of 5.47. Interestingly, the N-terminus of PIP is glutamine that is cyclized to form pyroglutamine which in turn, is not accessible for N-terminal amino acid sequencing [56]. Experimentally, PIP showed a band on SDS-PAGE corresponds to 20 000 Da, which is relatively high as compared to the calculated mass of 13 506 Da revealing the high carbohydrate content (approximately 22 %) as determined by Schaller et al [27].…”
Section: Primary Structure Of Pipmentioning
confidence: 91%
See 1 more Smart Citation
“…After the cleavage of signal peptide (28 amino acid residues) the mature polypeptide is 118 residues long with theoretical molecular mass of 13 kDa and pI of 5.47. Interestingly, the N-terminus of PIP is glutamine that is cyclized to form pyroglutamine which in turn, is not accessible for N-terminal amino acid sequencing [56]. Experimentally, PIP showed a band on SDS-PAGE corresponds to 20 000 Da, which is relatively high as compared to the calculated mass of 13 506 Da revealing the high carbohydrate content (approximately 22 %) as determined by Schaller et al [27].…”
Section: Primary Structure Of Pipmentioning
confidence: 91%
“…It was found that PIP binds to IgG via its Fc fragment. Recently, we have isolated a naturally occurring complex of PIP with ZAG [56] and determined its crystal structure. Our crystallographic analysis suggests that PIP is present in the cleft formed by domain a1-a2 and a3 platform of ZAG and provide a structural organization which is quite similar to an MHC-like arrangement where PIP is placed at the b2M site.…”
Section: Pip Binding Proteinsmentioning
confidence: 99%
“…The function of PIP is not known, but it is suspected to play a role in host defense against pathogens [1][2][3][4][5][6] because it is expressed in tissues strategically located at several Correspondence: Dr. Jude E. Uzonna e-mail: jude.uzonna@med.umanitoba.ca ports of pathogen entry, including the skin, eyes, and mouth [7]. Although a definitive evidence showing a role for PIP in host immunity is lacking, its ability to potentially bind with several important host molecules including CD4 + T-cell receptor, IgG, actin, zinc α2-glycoprotein, fibronectin, and enamel pellicle suggests it may have important biological functions [8][9][10][11][12][13]. Indeed, it has been shown that PIP is a ligand of the CD4 molecule and a potent inhibitor of * These authors contributed equally to this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Isoforms of ZAG along with PAP and PIP were also found to be assembled, making a large PPI network in this MPC. The native ZAG-PIP complex is already reported in our previous work [38,39]; PSA is also reported to form complexes individually with other seminal plasma proteins [40,41]. PIP is an aspartyl protease and known to cleave fibronectin.…”
Section: Discussionmentioning
confidence: 64%